GENERAL APPROACHES TO THE CREATION OF HYBRID TECHNOLOGY FOR NATIONAL GUARDS - Kondratenko, О. P. (Honor and Law, 2019)
The options for constructing various models of military caterpillar and wheeled vehicles equipped with an electric transmission and a hybrid power plant are discussed. The results of the analysis of the state and prospects of development of hybrid vehicles in the leading countries of the world are presented. The possibilities of energy recovery depending on the mass and mode of vehicle movement are determined.